Outpatient care for adolescents’ and young adults’ mental health: promoting self- and others’ understanding through a metacognitive interpersonal therapy-informed psychological intervention - Marconi, Elisa; Monti, Laura; Fredda, Giulia; Kotzalidis, Georgios D.; Janiri, Delfina; Zani, Valentina; Vitaletti, Debora; Simone, Maria Velia; Piciollo, Simone; Moriconi, Federica; Di Pietro, Emanuela; Popolo, Raffaele; et al. (Frontiers in Psychiatry, 2023)
Introduction Psychological distress may result in impairment and difficulty understanding oneself and others. Thus, addressing metacognitive issues in psychotherapy may improve psychopathology in adolescents and young adults (AYAs). We aimed to compare metacognitive interpersonal therapy (MIT)-informed psychotherapy with other treatment-as-usual (TAU) therapies. Methods We administered the Global Assessment of Functioning (GAF) scale, the Clinical Global Impressions–Severity (CGI-S) scale, and the Brief Psychiatric Rating Scale (BPRS) at baseline (BL) and at treatment termination (the endpoint was at 6 months and any last results obtained before that term were carried forward in analyzes). Patients received concomitant psychiatric and psychological treatment. Results Sixty AYAs were involved in the study. There was a significant reduction in symptomatology after the intervention. Twelve patients (17%) dropped out; treatment adherence was 83%. In the MIT group, 2 patients dropped out (11%), and in the TAU group, 9 patients dropped out (19%). All scales showed a significant reduction in symptoms between baseline (BL) and the 6-month endpoint: GAF (χ2 = 6.61, p < 0.001), BPRS (χ2 = 6.77, p < 0.001), and CGI (χ2 = 7.20, p < 0.001). There was a greater efficacy for the MIT group in terms of symptom reduction on the BPRS (t = 2.31; p < 0.05). Conclusion The study confirmed the efficacy of early and integrated care in adolescence and suggested greater symptom reduction for a psychotherapeutic intervention focused on stimulating mentalization skills. The study indicates the usefulness of this type of approach in the treatment of adolescent psychopathology. Due to the small sample size, the results need replication.